2014
DOI: 10.1039/c3mt00244f
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a possible dietary effect on the isotopic composition of Zn in blood via isotopic analysis of food products by multi-collector ICP-mass spectrometry

Abstract: In this work, the hypothesis of a possible dietary effect on the isotopic composition of Zn in blood from populations with different feeding habits, i.e. lacto-ovo vegetarians and omnivores, was investigated through isotopic analysis of Zn in common food products by multi-collector ICP - mass spectrometry (MC-ICP-MS). Several certified reference materials (CRMs) were also included in the sample set for comparison purposes. For these CRMs, the isotopic composition of Zn is expressed as δ-values, calculated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
47
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 32 publications
5
47
0
Order By: Relevance
“…2). For the bovine muscle, our δ 66/64 Zn result of −0.30 ± 0.10‰ agrees with data from a different laboratory (−0.24 ± 0.02‰ [22]). For BCR-639, the average δ 66/64 Zn value found was −3.29 ± 0.12‰, with no difference between the two batches (−3.31 ± 0.13 and 3.28 ± 0.11‰).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…2). For the bovine muscle, our δ 66/64 Zn result of −0.30 ± 0.10‰ agrees with data from a different laboratory (−0.24 ± 0.02‰ [22]). For BCR-639, the average δ 66/64 Zn value found was −3.29 ± 0.12‰, with no difference between the two batches (−3.31 ± 0.13 and 3.28 ± 0.11‰).…”
Section: Resultssupporting
confidence: 90%
“…For the human blood serum, the results are plotted on a different y -axis, due to the large isotopic offset. The δ 66/64 Zn literature data for London Zn, bovine muscle and human blood serum are from Moeller et al 2012 [58], Costas-Rodríguez et al 2014 [22] and Larner et al 2015 [21], respectively …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[14][15][16] To date, a number of ion exchange chromatographic protocols for specific sample types such as rocks, sediments, marine and fresh water, aerosols, plants and food has been published. [17][18][19][20][21][22][23][24][25][26] Moreover, our understanding about instrumental controls of mass bias including effect of acid strength, dopant/analyte ratios, wet and dry plasma and matrix has improved. [27][28][29][30][31][32] However, the rapid advance of the stable metal isotope field has not been accompanied by the supply of reference materials (RMs), hindering the inter-laboratory studies and quality assurances.…”
Section: Introductionmentioning
confidence: 99%
“…526 Costas-Rodriguez et al have shown recently that the difference in the isotopic composition of whole-blood Zn between omnivores and vegetarians is linked with the isotopic composition of food products of plant and animal origin, respectively. 527 Van Heghe et al demonstrated that menstruation and the associated loss of mineral elements are at the basis of the gender-based difference in whole blood Fe and Cu isotopic compositions. 528 Postmenopausal women show isotopic signatures that correspond with those of the male cohort of the population.…”
Section: Applications In Life Sciencesmentioning
confidence: 98%